Syzing and Analisys of a Photovoltaic System For Self-Consumption - Santos, César Manuel Sousa (Neutro à Terra, 2024)
The use of photovoltaic systems is a key aspect for a sustainable energy future because allows the use of renewable energy, prevenient from the Sun, to produce the electricity needed. The present paper proposes the sizing of a PV system and his analysis to see how much impact it has on a company energy footprint and how much money they can save by not using electricity from the grid. For this project was used a simulator provided by SMA, showing that it’s possible to invest on a PV system and get the payback in a few years.